L-lysine determination in animal feed using microbiological microtiter plate assay - JAKŠIĆ, S.; JAJIĆ, I.; KRSTOVIĆ, S.; MIHALJEV, Ž. (Journal of the Hellenic Veterinary Medical Society, 2018)
Chromatographic methods are most commonly used for the analysis of amino acids; however, there is growing need for faster, simpler and more price-effective assays. In this paper, the applicability of a rapid microbiological assay for quantification of the total content of L-lysine in feed samples was evaluated. The assay relies on the dependency of bacterial growth of Pediococcus acidilactici on the presence of L-lysine. Microbiological microtiter plate assay method for the quantitative determination of total (added and natural) L-lysine in feed samples has been verified, and parameters such as accuracy, precision, limit of detection, and limit of determination were evaluated. Results of total L-lysine determination in different feed samples have been compared with results of validated HPLC method. The microbiological microtiter plate assay method can be employed as a qualitative and quantification method for total L-lysine determination with detection and determination limit of 0.040 % and 0.085 %, respectively. However, further research on the influence of sample matrix on the determination of low lysine levels is required.